2020
DOI: 10.1101/2020.10.06.327445
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic discovery and functional interrogation of SARS-CoV-2 viral RNA-host protein interactions during infection

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the cause of a pandemic with growing global mortality. There is an urgent need to understand the molecular pathways required for host infection and anti-viral immunity. Using comprehensive identification of RNA-binding proteins by mass spectrometry (ChIRP-MS), we identified 309 host proteins that bind the SARS-CoV-2 RNA during active infection. Integration of this data with viral ChIRP-MS data from three other positive-sense RNA viruses defined pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 68 publications
4
33
1
Order By: Relevance
“…After our work was posted on the bioRxiv, R. Nchioua and colleagues have shown the importance of ZAP in controlling the response against SARS-CoV-2 [44] by demonstrating that a knock-out of this protein increases SARS-CoV-2 replication. The interaction between SARS-CoV-2 and ZAP has also been observed with unbiased methods in another recent work [45]. This finding supports our prediction that recognition of SARS-CoV-2 by ZAP imposes a significant fitness cost on the virus, as demonstrated by its early evolution to remove ZAP recognition motifs.…”
Section: Discussionsupporting
confidence: 90%
“…After our work was posted on the bioRxiv, R. Nchioua and colleagues have shown the importance of ZAP in controlling the response against SARS-CoV-2 [44] by demonstrating that a knock-out of this protein increases SARS-CoV-2 replication. The interaction between SARS-CoV-2 and ZAP has also been observed with unbiased methods in another recent work [45]. This finding supports our prediction that recognition of SARS-CoV-2 by ZAP imposes a significant fitness cost on the virus, as demonstrated by its early evolution to remove ZAP recognition motifs.…”
Section: Discussionsupporting
confidence: 90%
“…SNORD27 is one of the strongest host interaction partners for SARS-CoV-2 RNA ( Figure 6a ) and is traditionally known to guide 2’-O-methylation of 18S ribosomal RNA 42 . As snoRNAs can bind and methylate cellular RNAs 43 , and methylation enzymes including fibrillarin (FBL), rRNA methyltransferase 2 and 3 (MRM2 and MRM3) have been found to be physically associated with SARS-CoV-2 genome 23 , we tested whether SARS-CoV-2 RNA could be 2’-O-methylated and whether host RNAs’ methylation levels are changed upon virus infection. We performed 2 biological replicates of Nm-seq on total RNA from Hela cells, as well as from uninfected and SARS-CoV-2 infected Vero-E6 cells ( Supp.…”
Section: Resultsmentioning
confidence: 99%
“…. In addition, previous studies have also shown that SNORD27 and mitochondrial RNAs are enriched on SARS-CoV-2 using formaldehyde crosslinking, and sequencing23 . However, it is unclear if these RNAs bind to the genome directly or indirectly through protein interactions.…”
mentioning
confidence: 82%
“…SHFL (also known as RyDEN), previously reported to inhibit the programmed -1 ribosomal frameshifting in human immunodeficiency virus (HIV) infections [83], was further shown to be able to inhibit ribosomal frameshifting by the SARS-CoV-2 FSE in a dual-color fluorescence reporter system. Interestingly, while the ZIKV and DENV genomes were found to be robustly associated with N6-methyladenosine (m 6 A) readers of the YTHDF family, and depleted of interactions with m 6 A erasers of the ALKBH family, the SARS-CoV-2 genome showed the opposite trend, suggesting that SARS-CoV-2 might escape m 6 A methylation to increase the gRNA stability [31]. Oppositely, a specific interaction with the mitochondrial 2 0 -O-methyltransferase MRM2 was observed, in agreement with the physical localization of the SARS-CoV-2 gRNA to mitochondria, as suggested by a recent machine learning analysis revealing the presence of several mitochondrial-localization signals in the 5 0 UTR of the SARS-CoV-2 genome [84].…”
Section: Additional Insights From Transcriptome-wide Studiesmentioning
confidence: 99%
“…Over the past few months, enormous efforts have been put in trying to better understand the biology of the SARS-CoV-2 virus, to find an Achilles' heel and to confine the COVID-19 pandemic. In a very short time, the structure and function of the SARS-CoV-2 proteome [21][22][23][24][25], transcriptome [26], as well as the interactions with the host cell proteome, both at the protein [27][28][29] and RNA levels [30,31], have been dissected. We will here summarize the current knowledge on coronavirus RNA structures and their regulation, as well as the most recent discoveries, as revealed by cutting-edge high-throughput analyses conducted on SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%